2022
DOI: 10.1021/acs.jpclett.2c02500
|View full text |Cite
|
Sign up to set email alerts
|

Spacer Switched Two-Dimensional Tin Bromide Perovskites Leading to Ambient-Stable Near-Unity Photoluminescence Quantum Yield

Abstract: Semiconductor nanostructures with near-unity photoluminescence quantum yields (PLQYs) are imperative for light-emitting diodes and display devices. A PLQY of 99.7 ± 0.3% has been obtained by stabilizing 91% Sn2+ in the Dion–Jacobson (8N8)­SnBr4 (8N8-DJ) perovskite with 1,8-diaminooctane (8N8) spacer. The PLQY is favored by a longer spacer molecule and out-of-plane octahedral tilting. The PLQY shows one-month ambient stability under high relative humidity (RH) and temperature. With n-octylamine (8N) spacer, Rud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 60 publications
1
33
1
Order By: Relevance
“…These features are in stark contrast to the broad and redshifted self-trapped excitonic (STE) emission bands. 36 The optical properties of the AIP NCs mostly remain unchanged between the dispersed solution and the films, prepared by drop-casting or spin-coating the NC solutions (Figure 2a). 29 It has been observed that the absorption and emission spectra of the CsPbBr 3 NCs shift to energies lower than those of the corresponding NSs, because of a NC edge length higher than the NS thickness (Figure 2b).…”
Section: Optical Properties Of the Perovskite Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are in stark contrast to the broad and redshifted self-trapped excitonic (STE) emission bands. 36 The optical properties of the AIP NCs mostly remain unchanged between the dispersed solution and the films, prepared by drop-casting or spin-coating the NC solutions (Figure 2a). 29 It has been observed that the absorption and emission spectra of the CsPbBr 3 NCs shift to energies lower than those of the corresponding NSs, because of a NC edge length higher than the NS thickness (Figure 2b).…”
Section: Optical Properties Of the Perovskite Filmsmentioning
confidence: 99%
“…39 With a lowering of temperature, the number of phonon modes of 2D or 3D perovskites decreases, and at a temperature of ∼10 K, the line width is due to the inhomogeneous broadening. 36…”
Section: Optical Properties Of the Perovskite Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these alternatives, Sn-based perovskites showed great potential, but unfortunately, the rapid oxidations of Sn 2+ and Sn 4+ drastically hinder their stability and, hence, their applicability [ 10 , 11 , 12 ]. However, for 2D Sn-based Ruddlesden-Popper perovskites, the sizes and configurations of organic spacer cations have remarkable effects on the properties of these materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zero-dimensional (0D) metal–organic hybrids (MOH) have received increasing attention in research areas including light-emitting diodes (LED), photodetectors, and scintillators because of their excellent optoelectronic properties and high photoluminescence quantum yields. It has been demonstrated that Pb 2+ - and Sn 2+ -based hybrid systems show excellent PLQY and remarkable performance in X-ray scintillation. ,, However, while the toxicity of lead (Pb 2+ ) limits their industrial applications, Sn 2+ -based systems suffer from poor stability, even in the presence of a trace amount of moisture. , Subsequently, 0D hybrids based on Co 2+ , Ge 2+ , Bi 3+ , etc. were also explored, but the low PLQY and poor stability of these systems are the major bottlenecks. Recently, Mn 2+ -based 0D hybrid materials have shown great promise in light-emitting diode and photodetector applications, due to their greater stability and extremely high PLQY. , The emission color of Mn 2+ depends on its coordination environment, and the emission arises from the d–d spin-forbidden 4 T 1 → 6 A 1 transition.…”
mentioning
confidence: 99%